THE INFLUENCE OF SELF-CONCEPT AND LEARNING MOTIVATION ON SKILL OF LISTENING TO THE ENGLISH NARRATIVE - Fransisca Ambar Safitri; Gustaman Saragih (Universitas Indraprasta PGRI, 2021)
This research aims to understand: 1) The effect of self-concept and learning motivation in English narrative listening skills, 2) self-concept towards English reading, 3) The effect of learning motivation towards English narrative listening skills. The method used in this research is a survey using correlational and regression analysis techniques. The population in this research was 1015 students. The sample in this research was 100 students. The study results conclude that: 1) There was a significant effect of self-concept and learning motivation towards English narrative listening skills. Sig can prove that 0,000 <0.05 and Fcount = 20.325. 2) There was a significant effect of self-concept towards English narrative listening skills. The Sig proves that 0.002 <0.05 and tcount = 3.246. 3) There was a significant effect of learning motivation towards English narrative listening skills. The Sig proves 0,000 <0.05 and tcount = 4,617.Keywords: self-concept, learning motivation, English narrative listening skill